Nyai Shinta Ratri's Leadership Pattern in Improving the Quality of Islamic Education in A Waria Boarding School - Hak, M. Aji Asnal; Kholik, Nur; Salim , Ahmad (DAS Institute, 2024)
Islamic boarding school plays an important role in the education system in Indonesia. This study aimed to find out the leadership pattern of Nyai Shinta Ratri, as well as the supporting and inhibiting factors in improving the quality of Islamic education of the students. The method used in this research is descriptive qualitative. The subjects in this study were the boarding school administrators, students, and the surrounding community. The data of this study used to explore the observation, interviews, and documentation. Data validity techniques using triangulation techniques and source triangulation methods. While in the data analysis technique is done by data reduction, data presentation, and conclusion drawing. The results of this study show: 1) the leadership pattern used by Mrs. Nyai Shinta Ratri is a democratic leadership type, it is shown through the relationship between the caregiver and the students is well established. In making decisions, Mrs. Nyai Shinta Ratri always involves team members so as to minimize the risk of wrong and hasty decisions. 2) Supporting factors in improving the quality of Islamic education of the students are the experience and knowledge possessed by the caregivers.